First 3D reconstruction and volumetric body mass estimate of the tapinocephalid dinocephalian Tapinocaninus pamelae (Synapsida: Therapsida). (3rd April 2021) - Romano, Marco; Rubidge, Bruce
ABSTRACT: Dinocephalians were the earliest large terrestrial tetrapods from Gondwana, making this group crucial in understanding body mass (BM) evolution in basal synapsids, but no detailed weight determinations are available for the clade. Here we present the first BM estimate for a dinocephalian on the basis of the remarkably well preserved and complete skeleton of the basal tapinocephalid Tapinocaninus pamelae from the lowermost Beaufort Group of South Africa. We reconstructed three 3D models of Tapinocaninus using mounted skeletons of the dinocephalians Moschops and Ulemosaurus to reconstruct the missing elements. Applying a density range between 0.9 and 1.15 Kg/1000 cm 3 for living tissue to the model we reconstructed an average BM of 892.63 Kg for the taxon. Classic regression formulae, based on humerus and femur circumference, provide higher values of 1694.5 Kg and 2015.8 Kg, with an overestimation of 90% and 126% respectively. The study confirms that volumetric BM estimates are more precise, and are recommended if relatively complete skeletons are available. The 'intermediate' posture recognized for Tapinocaninus, more upright with respect to the sprawling condition characterizing sphenacodontid 'pelycosaurs', could represent a response to a large BM, which, for the first time in synapsids, reaches weights close to a tonne.